Cesarean scar defect and its association with clinical symptoms, uterine position and the number of cesarean sections - B., Madhangi V.; C., Ramany (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean scar defect (CSD), also called isthmocele or niche is a long-term complication, which can be asymptomatic or can give rise to chronic pelvic pain, dyspareunia and postmenstrual spotting. The objective of this study was to assess the association of CSD with clinical symptoms, position of the uterus and the number of caesarean sections. Methods: This was a prospective observational study done at a tertiary care teaching hospital from January 2019 to December 2019. The study included women with history of previous one or more caesarean sections with demonstrable CSD on transvaginal ultrasound. Various scar dimensions noted were width and depth of the scar. A deficiency ratio was calculated as a ratio of residual myometrium at the scar to the adjacent myometrium. Univariate analysis was done to assess the relationship of clinical symptoms with the defect parameters and number of previous caesarean sections. Multiple logistic regression analysis was done to find out the association between symptoms and number of previous caesarean sections with the scar defect dimensions. Results: The width, depth and deficiency ratio of the CSD were significantly higher in study subjects with a greater number of caesarean sections. Retroflexed uteri had larger CSD. There was no association of clinical features with the defect dimensions and the position of the uterus. Conclusions: CSD dimensions and deficiency ratio correlate with the number of previous caesarean sections and the position of the uterus. There was no association of clinical symptoms with the defect parameters.